Ethnopharmacological survey of medicinal plants used for the management of pediatric ailments in Kano State, Nigeria - U.S. Abubakar; K.M. Yusuf; G.T. Abdu; S.R. Saidu; G.A. Jamila; A. Fatima (Iranian Society of Pharmacognosy, 2017)
Background and objectives: The knowledge of traditional uses of plant species used in the management of pediatric diseases in Kano State is still intact with the traditional healers; thus, the present study was aimed to collect, identify and document plant species used traditionally for the management of pediatric diseases in the study area. Methods: The ethnobotanical data was collected through informal interviews with the traditional medicine practitioners, traditional birth attendants, herb sellers and some health workers. Results: A total number of sixty eight plant species belonging to thirty five families were reported to be used in the disease management among children in the study area. Most of the plants species belonged to the Fabaceae, Poaceae, Anarcadiaceae, Asteraceae, Combretaceae and Solanaceae families, while Anogeissus leiocarpus, Boswellia dalzielii and Citrus sinensis were the most frequently mentioned plant species. Leaves and stem bark were the most used plant parts in this study. Conclusions: Further studies should be conducted to evaluate the pharmacological activities of the plant species that have not yet been investigated and also to identify the phytochemical constituents responsible for their activities.